Analisa Effectiveness Mesin Threser Di PTPN V Sei Garo Menggunakan Metode Analytical Hierarchy Process (AHP) - Aria, Dedek; Susilawati, Anita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
This research is aimed to analyze production process at threser station using Overall Equipment Effectiveness (OEE) and AHP methods in PTPN V Sei.Garo factory. The research methodology consists of three main steps: (1) gathered data, (2) calculate the OEE values to analyze the losses, (3) evaluated the big losses using the AHP method. The calculation of the OEE values based on the 6 months data period, from March to August 2017. There were six big losses analysed in this research i.e.: breakdown losses, setup and adjustment losses, idling and minor stoppage losses, reduced speed losses, rework losses and reduced yield losses. A loss analysis can be indicated in low OEE values result. From the analysis of OEE calculation results were obtained the OEE values rate of the threser machine during research period of 74.11%. It was below the world class standard (below 85%). Result of the analysis of six big losses was obtained the significant losses affect the OEE value of idle minor losses. The high idle and minor losses of the threser machine should be removed by determine action to minimize the causes of losses. Furthermore, it was chose the alternative action to overcome the highest losses using Analytical Hierarchy Process (AHP) method. The result shown alternative weighted data to reduced the idle and minor losses priority of periodically checking (0.29), SOP application (0.28), retraining (0.27), and maintain cleanliness (0.15). Therefore, to reduced the losses and improve the effectiveness of threser station can be implemented Total Productive Maintenance (TPM) pillars such as focused maintenance (periodically check the machine components) and autonomous maintenance.Keywords: OEE, Threser machine, Analytical Hierarchy Process